2015
DOI: 10.1177/2332649215608873
|View full text |Cite
|
Sign up to set email alerts
|

The Racial Gap in Childhood Blood Lead Levels Related to Socioeconomic Position of Residence in Metropolitan Detroit

Abstract: Childhood lead poisoning in the United States remains a persistent, prevalent environmental public health problem, especially for children living in central-city neighborhoods. These neighborhoods typically are racially segregated, are in proximity to current and/or legacy lead emission sources, consist of older housing, and contain disproportionately African American or black children of low-income families. This research had two aims: (1) to determine whether average blood lead levels (BLLs) in children in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 47 publications
(63 reference statements)
2
31
1
Order By: Relevance
“…Vivier et al (2011) andKrieger et al (2003) show that more than 30% of children in the poorest neighborhoods in Rhode Island had lead levels exceeding 10 µg/dL. Moody et al (2016) report that children living in predominantly black and low-income segregated neighborhoods in Detroit had the highest average blood lead levels in the city, although there was no gap between black and white children in the poorest neighborhoods (see also Kaplowitz et al 2010). Sampson & Winter (2016), in contrast, report that the racial disparity in blood lead in Chicago persisted even after adjusting their estimates for neighborhood-level education, poverty, and the age, vacancy, and dilapidation of neighborhood housing.…”
Section: Inequality In Lead Exposurementioning
confidence: 99%
“…Vivier et al (2011) andKrieger et al (2003) show that more than 30% of children in the poorest neighborhoods in Rhode Island had lead levels exceeding 10 µg/dL. Moody et al (2016) report that children living in predominantly black and low-income segregated neighborhoods in Detroit had the highest average blood lead levels in the city, although there was no gap between black and white children in the poorest neighborhoods (see also Kaplowitz et al 2010). Sampson & Winter (2016), in contrast, report that the racial disparity in blood lead in Chicago persisted even after adjusting their estimates for neighborhood-level education, poverty, and the age, vacancy, and dilapidation of neighborhood housing.…”
Section: Inequality In Lead Exposurementioning
confidence: 99%
“…22,43 Furthermore, due to a prior breach in patient confidentiality of children's BLLs at the address level, the State of Michigan's IRB policy prohibits a finer level of geography provided by the MDCH in order to maintain confidentiality of each case.…”
Section: Pediatric Bll Datamentioning
confidence: 99%
“…This phenomenon is explored in more detail below. Multiple regression and hierarchical linear modeling analyses of a variety of variants at both the individual level and census tract level resulted in colinearities and unacceptable residual patterns as described in more detail in Moody et al 22 No doubt, the CDC's policy of recording non-detectable values as a 1.0 μg/dL and the influence of a variety of variables at a larger census tract scale of geography are contributors.…”
Section: Bivariate Regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Smith [ 10 ] showed that the DMA’s poor and black neighborhoods were strong predictors for EPA’s Superfund site locations. Lastly, Moody et al [ 11 , 12 ] found that in the DMA, black segregated neighborhoods with lower socioeconomic characteristics were strong predictors of elevated blood lead levels (BLLs) in children residing in those areas.…”
Section: Introductionmentioning
confidence: 99%